Pengaruh Persepsi dan Media Sosial Instagram Terhadap Keputusan Berkunjung ke Museum Konperensi Asia Afrika Bandung - Jane Angelina Naseng; Nova Riana; Khoirul Fajri (STIEPAR YAPARI Bandung, 2023)
The level of tourists visits at Museum of The Asia-Africa Conference (MKAA), Bandung had been fluctuated in the last 3 years from 2019-2022. The factor that influenced this fluctuation were the Covid-19 Pandemic over the past few years which decreased the level of tourists visits, also, as well as the tourists perception about the service of MKAA. The purpose of this study was to determine visitor perceptions, Instagram social media, visiting decisions and find out the influence between visitor perceptions and Instagram social media on the decision to visit The Museum of Asia-African Conference. This research was conducted at Museum of The Asia-Africa Conference with number of sample at 100 respondents taken from the population. This study conducted in descriptive, verifiable and multiple linear regression methods, counted by using SPSS 25.0 software. As results of research, visitor perception is in the